(untitled) (Experimental biology, 2022)
One of the most important factors that has a significant impact on the health of the population of the Republic of Kazakhstan is a violation of the diet due to insufficient consumption of full–fledged proteins, vitamins, macro- and microelements and their irrational ratio. In Kazakhstan, grain crops are produced in large volumes, but there is no production of beverages based on vegetable raw materials, although the production of vegetable milk is already widespread throughout the world. The use of local vegetable raw materials from different regions of Kazakhstan in the production technology of grain milk drinks is an urgent and promising direction in the food industry. The article presents the results of a study of the quality of buckwheat breeding varieties "Shortandinskaya", "Batyr" and "Saulyk". During the study, buckwheat samples were evaluated physico-chemical, technological properties and safety indicators. All the studied samples of buckwheat grains in terms of safety meet the requirements of the Technical Regulations of the Customs Union "On grain safety". The scientific data obtained during the implementation of the project will become the basis for the creation of new grain "milk" drinks enriched with Omega-3 polyunsaturated fatty acids. The result of the implementation of this research will be the expansion of the range of beverages for healthy and safe nutrition of the population.